O PROCESSO EDUCACIONAL DA CULTURA INDÍGENA TICUNA NA REGIÃO DO ALTO SOLIMÕES - Oliveira, Samuel Rocha de (2012)
This work analyzes the educational system in Ticuna tribe, located in the Alto Solimões, Amazonas state, where I have been working for 21 years in permanent contact with the Ticuna Indians. Over the years I have observed that every day, and more intensely, maintaining their culture has undergone the process of influence of non-Indian culture. This work is carried out a historical survey on the possible existence of two streams of education among Ticuna teachers.One considers an important bilingual education, the study of myths and customs for the preservation of culture, the other believes that it is harmless to study the myths and other cultural aspects that can be seized on a daily basis, they argue that the Indians need of equal education that of non-indigenous, to compete in the market on equal terms. Initially it is proposed a historical inquiry about the educational process related to Ticuna culture outside the school, trying to verify the relationship between what is transmitted by the school and that is evident in the daily Ticuna. It then performs an analysis of how education takes place in the middle Ticuna implanted under the heading "Indian Education". Noteworthy are the factors that influenced the founding of the school, its location and other aspects related to the physical, economic, social and cultural as well as the environment and human learning, data that support the proposed objective for this work. It seeks to determine whether education developed in indigenous school fulfills the role of constantly seeking alternatives to an education that is appropriate to the survival of the Ticuna culture, an education to the cultural reality. The research is based on survey data through documents, as well as in interviews with leaders, teachers and elders of the Ticuna tribe, also on direct observation, with notes taken in a field notebook. The process of assimilation and influence of non-Indian culture is dominant in the upper Amazon and has "crushed" Ticuna culture, so that many no longer want more fish, hunt and live as farmers or collectors. It is necessary to seek educational alternatives for Ticuna indigenous school in an education that is appropriate for the survival of their culture and at the same time minimize the prejudice faced by these people. Leaders and teachers Ticuna expect the school to help in the preservation and enhancement of their culture. The damage caused to the cultural education of the Indians Ticuna is large, the majority of children and young people are not knowledgeable of the meanings of religious rituals, myths, legends and beliefs. Often know to perform the ritual, but it seems more an imitation of gestures, which is releasing its real meaning. It is hoped that the end of this research we are able to use the material developed for reflection. It may serve as a starting point for teachers Ticuna in developing guidelines and development of a new educational paradigm that puts more emphasis on culture.